Multidrug-resistant organism infections and mortality: estimates from a large Italian hospital. (30th September 2020) - Moro, M; Vigezzi, G P; Callari, E; Biancardi, A; Nizzero, P; Cichero, P; Signorelli, C; Odone, A
Abstract: Background: Multidrug-resistant organisms (MDRO) are one of the most critical public health concerns, particularly in hospital settings. Nearly 8% of hospitalized patients develop healthcare-associated infections (HAI), 20% of which is caused by MDRO. Aim of the study was to estimate nosocomial infection-associated in-hospital mortality, by different MDRO, in a large Italian teaching hospital. Methods: We conducted a retrospective cohort study on patients hospitalized at San Raffaele Hospital, Milan, from 2016 to 2018. Two existing datasets were merged: hospital discharge records and MDRO surveillance data. Exposure was defined as any HAI caused by MDRO, and main outcome variable was in-hospital mortality from all causes. Results: A total of 78, 795 patients were studied (mean age 59.3 y, age range 18-105 y). 1, 345 patients with at least one MDRO had mean age of 68 y, mean length of stay (LOS) of 32.8 days and mean DRG weight of 3.8. 77, 450 patients without MDRO isolation had mean age of 59 y, mean LOS of 7.2 days and mean DRG weight of 1.6. Risk of in-hospital mortality is 3.4 times higher in patients with at least one MDRO isolation (OR 3.4; 95% CI 2.8-4.2). Enterococci (OR 2.6; 95% CI 1.1-6.3), A. baumannii (OR 3.5; 95% CI 1.4-8.6), P. aeruginosa (OR 1.8; 95% CI 0.8-4.2), MRSA (OR 3.4; 95% CI 2.1-5.4), ESBL-producing (OR 1.9; 95% CI 1.4-2.7) and carbapenem-resistant bacteria (OR 3.8; 95% CI 2.5-5.7), and carbapenem-resistant K. pneumoniae (OR 5.5; 95% CI 3.2-9.2) isolations were risk factors for nosocomial mortality. Conclusions: Patients with MDRO isolations were older, more complex and had 5 times longer LOS than ones without MDRO. Deceased patients were 18% among MDRO cohort against only 2% among others. Bacteria included in WHO list of priority pathogens with antibiotic resistance were associated with a significantly higher risk of death. These results prove the urgency of controlling MDROs' spread that threatens global public health and available treatments of infections. Key messages: Nosocomial MDRO isolation is a significant risk factor for in-hospital mortality from all causes. Infection prevention and control measures, and antibiotic stewardship are key strategies in order to prevent MDRO transmission and HAI, AR spreading and their burden of related deaths.